Pengaruh Penggunaan Media Flashcard Terhadap Kemampuan Membaca Permulaan Anak Kelompok B Di Tk Pertiwi Keprabon Polanharjo Klaten Tahun Ajaran 2015/2016 - Nindyawati, Anis Fadillah; , Dr. Darsinah, M. Si (2016)
Research on Group B TK Pertiwi Keprabon effected by the ability to read a wide variety of children. There is a child who is still a difficulty in distinguishing letters, to distinguish the sounds of letters and can not distinguish the same initial syllables. The purpose of this research is to know the influence of media use flashcard against reading the beginning of Group B in TK Pertiwi Keprabon Klaten Polanharjo academic year 2015/2016. The research is the research of design experiments with one group pretest-posttest. The subject in this study all Group B TK Pertiwi Keprabon totalling 29 children. Metod used data collection i.e. observation. Technique of data analysis using t-test analysis. results data indicate t calculate = table-t <-25,327 <-1.701 then Ho denied and Ha is received. Then it can be inferred that there is an influence of media flashcard against reading skills children beginning of group B in TK Pertiwi Keprabon Klaten Polanharjo academic year 2015/2016